Nail fold capillaroscopy in patients of systemic sclerosis and its association with disease severity as evidenced by high resolution computed tomography lung: a hospital based cross sectional study - Jehangir, Majid; Qayoom, Seema; Jeelani, Shazia; Yousuf, Rahil (International Journal of Research in Medical Sciences, 2017)
Background: The specific nail fold capillary (NFC) pattern found in systemic sclerosis (SSc), can be examined using a dermascope, which can prove as a simple and cost effective procedure for early diagnosis and proper management of patients with SSc. Methods: A case-control study was conducted on 65 subjects – 10 patients with primary raynauds phenomenon (RP), 40 patients with the SSc and 15 age and gender matched controls. Pattern of NFC using a dermascope was studied in all the subjects. HRCT lung was done in all the SSc patients and the findings were correlated with NFC pattern. Results: Out of the 65 subjects under study, Nail Fold Capillary (NFC) pattern was abnormal in (40/65) 61.54%. NFC changes were seen in all the (100%) patients of SSc. None of the patients with primary raynauds phenomenon had any positive findings on NFC. High resolution computed tomography (HRCT) lung in patients of SSc when correlated with NFC pattern revealed that overall 20 patients (50%) had interstitial lung disease (ILD). Only one patient with early sclerodermoid pattern of NFC showed ILD whereas 55% and 100% of the patients with active and late pattern of NFC respectively showed ILD on HRCT lungs. Conclusions: Our study serves to show that NFC pattern can be used as a screening tool in patients with history of RP for diagnosis of systemic sclerosis. The study has shown an association between advanced changes as observed in NFC pattern and systemic involvement in SSc patients as evidenced by HRCT lung.